2021
DOI: 10.3892/ol.2021.13096
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PBRM1 in VHL disease‑associated clear cell renal cell carcinoma and its putative relationship with the HIF pathway

Abstract: Von Hippel-Lindau (VHL) disease is the main cause of inherited clear-cell renal cell carcinoma (ccRCC) and is caused by germline mutations in the VHL tumor suppressor gene. Bi-allelic VHL alterations lead to inactivation of pVHL, which plays a major role by downstream activation of the hypoxia inducible factor (HIF) pathway. Somatic VHL mutations occur in 80% of sporadic ccRCC cases and the second most frequently mutated gene is polybromo 1 (PBRM1). As there is currently no data regarding PBRM1 involvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In our study, the loss of PBRM1 expression was not validated in patient 5 with strong nuclear positivity. Gad et al [ 24 ] recently reported increased PBRM1 expression with uniform and strong nuclear staining in Von Hippel-Lindau disease-associated clear cell renal cell carcinoma and a PBRM1 mutant case showing retained protein expression. Additionally, an ARID1A W1545* nonsense mutation (c.4634G>A, p.Trp1545*) was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the loss of PBRM1 expression was not validated in patient 5 with strong nuclear positivity. Gad et al [ 24 ] recently reported increased PBRM1 expression with uniform and strong nuclear staining in Von Hippel-Lindau disease-associated clear cell renal cell carcinoma and a PBRM1 mutant case showing retained protein expression. Additionally, an ARID1A W1545* nonsense mutation (c.4634G>A, p.Trp1545*) was observed.…”
Section: Discussionmentioning
confidence: 99%
“…HIF1α and HIF2α play an important role in ccRCC carcinogenesis. 16 Yang et al 17 revealed the effect of long non-coding RNALINC01234 on ccRCC. Knockout of LINC01234 inhibited the HIF-2α pathway, which led to decreased HIF-2α expression, and causing the inhibition of ccRCC cell growth and metastasis.…”
Section: Targeting Angiogenesismentioning
confidence: 99%
“…HIF-1a and HIF-2a are transcription factors that bind to the hypoxia response element (HRE), activating a myriad of genes involved in hypoxia adaptation [ 66 ]. In most cases of ccRCC, pVHL is inactivated, resulting in the accumulation of HIF-1a and HIF-2a and continual activation of HIF target genes, despite normal oxygen levels [ 67 , 68 ]. One of the most common targets of HIF1 is vascular endothelial growth factor (VEGF), which induces angiogenesis.…”
Section: Roles Of Evs In Rcc Progressionmentioning
confidence: 99%